Comparative Study of Service Quality Before and After the Implementation of the PLN Mobile Application at PT PLN (Persero) Customer Service Unit - Darmawan, Ketut Dody; Bagia, I Wayan (International Journal of Social Science and Business, 2022)
The rapid development of information technology recently has greatly influenced the needs of modern society for a service to be able to provide convenience, speed, and practicality in obtaining a service product. Besides, the situation of the Covid-19 pandemic has forced us to stay and reduce the outside activities nowadays for decreasing the clusters of the Covid-19 virus. Due to the demands, the company needs innovation to improve the service quality in keeping the satisfaction of the customer. This study was aimed to compare the service quality of customer before and after the implementation of the PLN Mobile at PT PLN (Persero) Kuta Badung Bali Service Unit. This quantitative research used a questionnaire method filled in via Google Form with a Cluster Random Sampling system. The data analysis technique used Paired Sample T-Test. The results showed: (1) The level of customer service quality in the PLN Manual was categorized as â€œEnoughâ€, means that it was ineffective in getting services from PT PLN (Persero) Kuta. (2) The level of customer service quality after the implementation of the PLN Mobile is categorized as "Very High", means that customers are satisfied in the efficiency time with PLN's services from PT PLN (Persero) Kuta. (3) There was a strong influence with a significant difference on the quality of customer service before and after the implementation of the PLN Mobile.